2019
DOI: 10.26487/hebr.v3i1.1836
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Avoidance, Risk Avoidance and Perceived Risk: A Cultural Perspective of Individual Investors

Abstract: Risk serves as an important aspect that can change the decision making of individuals, especially if it is related to investment decision making. The effects of risk on investment decision making have been extensively discussed in the literature but little of it assessed the dominance of various risk-related factors in investment decision making by individuals. In order to make up for this lack,  this research studies the impact of risk avoidance,  uncertainty avoidance and perceived risk on the investment int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
1
16
1
Order By: Relevance
“…Dawuda and Azeko (2015) explained that lack of accounting knowledge, inability to quantify the value of financial information, lack of financial education, and limited access to information may account for this reason. However, our finding disagrees with the findings of Arshad and Ibrahim (2019) who reported that Pakistani investors gather and analyze more information as a strategy to reduce risk. Li, Masuda, and Russel (2014) also echoed similar findings with Arshad and Ibrahim in their study of online financial decisionmaking process of East Asian and North American countries that Hong Kong Chinese, compared to European Canadians, spend time to parse through information before making financial decisions.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Dawuda and Azeko (2015) explained that lack of accounting knowledge, inability to quantify the value of financial information, lack of financial education, and limited access to information may account for this reason. However, our finding disagrees with the findings of Arshad and Ibrahim (2019) who reported that Pakistani investors gather and analyze more information as a strategy to reduce risk. Li, Masuda, and Russel (2014) also echoed similar findings with Arshad and Ibrahim in their study of online financial decisionmaking process of East Asian and North American countries that Hong Kong Chinese, compared to European Canadians, spend time to parse through information before making financial decisions.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that a great number of investors seemed to prefer short-duration investments to long-duration investments. Arshad and Ibrahim (2019) studied the investment behavior of Pakistani investors and found that risk avoidance and uncertainty avoidance significantly influence investment choices. They explained that Pakistani investors tend to estimate the financial loss they may incur as a result of their decisions and develop strategies to reduce or avoid the risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The moderate in-close (0.459) and out close (0.500) denotes moderate inflow and outflow of information from other factors. Arshad and Ibrahim (2019) found that culture is an important aspect in determining investors' risk perception towards equity shares.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, uncertainty avoidance refers to the degree to which people feel uncomfortable with ambiguity and an uncertain future (Hope 2003). Arshad and Ibrahim (2019) believe that Uncertainty Avoidance may be the most influential cultural aspect that affects PRP. Some researchers pointed out that the relationship between media consumption and PRP may be affected by the country type (Mazur 2006).…”
Section: Country Typementioning
confidence: 99%